Główne problemy zarządzania kosztami informatyki - Zygała, Ryszard (Some Important Problems with Information Technology Costs Management, 2007)
For many years expenditures on information technology have become an increasingly important part of organizations budgets. Based on the author's experience, CIO's and financial executives do not attach enough importance to building advanced solutions in order to identify, classify and measure total IT processes costs. Often, in practice, the problem with IT costs management is of organizational nature. In this paper, some important aspects of IT cost management are discussed from different perspectives.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 207-214